Marketing in the Digital Age - Adapting to Changing Consumer Behavior - Sharma, Sabin (MultiTech Publisher, 2024)
The digital age has transformed consumer-brand interactions, requiring a nuanced grasp of evolving digital consumer behaviors and expectations for effective marketing strategies. This study aims to investigate changing consumer behavior influenced by digital technologies and marketing. A descriptive cross-sectional study was conducted involving 204 respondents engaged in digital marketing technology. Self-administered questionnaire was distributed via Google Form through various social media platforms and emails, and collected data was analyzed using SPSS version 25. The findings revealed pervasive influence of digital platforms, with 79.9% awareness of digital marketing concepts and 94.1% making online purchases after encountering digital advertisements. Informed decision-making is found evident, as 86.3% review product information before online purchases, and 84.3% express trust in information from blogs and websites. The study found that the consumer perceptions of digital marketing, revealing positive sentiments towards content, satisfaction with social network marketing, and the role of digital media in aiding decision-making. The study highlights the significant impact of digital marketing on consumer behavior, emphasizing the need for businesses to strategically leverage social media, enhance online product information, and tailor marketing approaches to align with diverse consumer preferences.